PTU-135 An atypical complication of lymphocytic oesophagitis; images of a pseudo tracheo-oesophageal fistula. (22nd June 2015) - Manda, V; Sharp, C; Gibson, S; Robertson, K
Abstract : Introduction: In 2006 Lymphocytic Oesophagitis (LO) was characterised as a histologic subset of chronic oesophagitis. The pathognomonic feature is a peripapillary T-cell lymphocytic infiltrate. The commonest presenting symptom is dysphagia (75%) but it can also be with chest pain or reflux symptoms. Endoscopic findings are equally variable; normal mucosal appearance (30%), stricture (8.6%), 'trachealisation' (19.8%) and nodularity (3.7%). The endoscopic appearance of tracheo-oesophageal fistula has not been reported. Method: We present a photographic study of a 76-year old lady with symptoms of intermittent dysphagia for 7 years. She had multiple endoscopy procedures with balloon dilation of what were thought to be simple peptic strictures. Recurrent dysphagia associated with weight loss prompted further endoscopy in 2014. An11 mm scope could not be advanced beyond 20 cm at which level there was evidence of patent but narrowed, rigid oesophagus. There was 'trachealisation' similar to that seen with eosinophilic oesophagitis. Biopsies were taken which allowed a diagnosis of LO. Poor patient compliance delayed repeat endoscopy for 6 months. The stricture was as before but there was also an area of weakness that seemed to depress with inspiration and protrude on expiration (Figure 1) . The intention had been balloon dilation but with concern of a tracheo-oesophageal fistula it was not performed. Bronchoscopy, performed the next day, was normal. Results: Oral intake was resumed without symptoms of tracheo-oesophageal fistula. CT demonstrated an area of thickened oesophageal wall and barium swallow showed a small out pouching of the oesophagus in keeping with the defect identified at endoscopy. Although still struggling with dysphagia our patient remained well and, at her request, was allowed home. Subsequent endoscopy has shown the area to have healed though the stricture remains. Conclusion: Spontaneous perforation of the oesophagus has been reported as a complication of LO. Micro-abscesses have also been described and it is possible that an aggregation of these has resulted in perforation in that case and the appearance of a fistula seen in our case. LO is a very rare condition and we have much to learn of its pathophysiology. Disclosure of interest: None Declared.